2015
DOI: 10.1111/ppe.12249
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pre‐Pregnancy Body Mass Index and Gestational Weight Gain with Preterm Births and Fetal Size: an Observational Study from Lebanon

Abstract: High GWG increased the risk of LGA for all groups and PTB in normal weight and overweight women, whereas low GWG increased the risk of SGA and PTB. Given that there are not many studies from middle income/developing countries on patterns of weight gain during pregnancy, findings from this study may help with pre-conception counselling with emphasis on the importance of an optimal pre-pregnancy BMI and appropriate weight gain during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
25
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
(115 reference statements)
12
25
0
5
Order By: Relevance
“…Our result regarding extremely preterm birth is also consistent with results from a Swedish study [22]. A systematic review of studies from lowand middle-income countries reported that maternal underweight was significantly associated with an increased risk of preterm birth [15], and a hospital-based study from Lebanon also indicated an increased risk of preterm birth only among underweight women with low GWG [23]. The inconsistent results could be due to the different ethnicities.…”
Section: Discussion/conclusionsupporting
confidence: 86%
“…Our result regarding extremely preterm birth is also consistent with results from a Swedish study [22]. A systematic review of studies from lowand middle-income countries reported that maternal underweight was significantly associated with an increased risk of preterm birth [15], and a hospital-based study from Lebanon also indicated an increased risk of preterm birth only among underweight women with low GWG [23]. The inconsistent results could be due to the different ethnicities.…”
Section: Discussion/conclusionsupporting
confidence: 86%
“…Our findings help to explain the inconsistent findings between pre-pregnancy BMI and PTB outcomes reported in previous studies202122232425262728 and suggest that such inconsistency may be partly due to the interactions between maternal genotype (that is, rs11161721) and pre-pregnancy BMI. We showed that the impact of pre-pregnancy BMI on overall PTB risk depends on the maternal genotype at rs11161721.…”
Section: Discussionsupporting
confidence: 51%
“…First, maternal pre-pregnancy overweight/obesity (OWO) is prevalent in the BBC (>50%), which is significant from clinical and public health perspectives, and also ensures sufficient statistical power to identify a significant G × E interaction in this study. In addition, previous studies on the associations of pre-pregnancy BMI or OWO with PTB have yielded inconsistent results, including positive20212223, null2425 or negative associations262728. It is possible that such inconsistent findings may be in part due to maternal gene × pre-pregnancy BMI interaction29, which is largely unexplored.…”
mentioning
confidence: 99%
“…Preterm Birth  Cigarette smoking (Bottorff et al, 2014)  Cigarette smoking (Koullali et al, 2016)  Exposure to environmental tobacco (Ashford et al, 2010;Crane et al, 2011;Savitz & Murnane, 2010)  Alcohol, cannabis and other illicit drug use (Salas-Wright et al, 2015)  Cannabis use (Prunet et al, 2016)  Sub-optimal nutrition (Bloomfield, 2011)  Inappropriate gestational weight gain (Haggarty et al, 2009;Harper et al, 2011)  Low/high body mass index (Koullali et al, 2016)  Inappropriate gestational weight gain (El Rafei et al, 2016)  Maternal anxiety and/or depression (Siegel & Brandon, 2014)  Maternal anxiety (Liou et al, 2016)  Maternal depression (Accortt et al, 2014)  Stress (Straub et al, 2014)  Intimate partner violence (Edirne et al, 2010;O'Donnell et al, 2009)  Intimate partner violence (Donovan et al, 2016)  'Inadequate' antenatal care (Debiec et al, 2010;Raatikainen et al, 2007)  'Inadequate' antenatal care (Prunet et al, 2016)  Genito-urinary infection (Goyal et al, 2016)  Genito-urinary infection (Sangkomkamhang et al, 2008)…”
Section: Adolescent Pregnancymentioning
confidence: 99%